Conserving Caribbean beaches - Cambers, Gillian (2008)
Explains how increasingly frequent and fierce hurricanes and storms are contributing to coastal erosion in the Caribbean. Cautions that measures taken in response to erosion itself may worsen the problem of erosion elsewhere.